2002
DOI: 10.2337/diabetes.51.12.3440
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Activated Protein Kinase-Independent Potentiation of Insulin Secretion by cAMP Is Impaired in SUR1 Null Islets

Abstract: Whereas the loss of ATP-sensitive K؉ channel (K ATP channel) activity in human pancreatic ␤-cells causes severe hypoglycemia in certain forms of hyperinsulinemic hypoglycemia, similar channel loss in sulfonylurea receptor-1 (SUR1) and Kir6.2 null mice yields a milder phenotype that is characterized by normoglycemia, unless the animals are stressed. While investigating potential compensatory mechanisms, we found that incretins, specifically glucagon-like peptide-1 (GLP-1) and glucosedependent insulinotropic pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 66 publications
12
90
5
Order By: Relevance
“…Several studies have proposed roles for EPAC and͞or its effector Rap1 in cAMP-induced processes, such as regulation of the H ϩ ͞ K ϩ -ATPase in rat kidney cortical collecting duct cells (19) or insulin secretion by pancreatic islets (20,21). The aim of this work was to study the contribution of the EPAC-and PKA-dependent pathways to the cAMP-induced inhibition of NHE3 and NaPi-IIa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have proposed roles for EPAC and͞or its effector Rap1 in cAMP-induced processes, such as regulation of the H ϩ ͞ K ϩ -ATPase in rat kidney cortical collecting duct cells (19) or insulin secretion by pancreatic islets (20,21). The aim of this work was to study the contribution of the EPAC-and PKA-dependent pathways to the cAMP-induced inhibition of NHE3 and NaPi-IIa.…”
Section: Resultsmentioning
confidence: 99%
“…A role of EPAC in several cAMP-regulated processes such as cell adhesion and migration (16), insulin secretion (20,21), and regulation of the H ϩ ͞K ϩ -ATPase in the kidney cortical collecting duct (19) has been already demonstrated. Several intracellular cascades may mediate these effects.…”
Section: Regulation Of Sodium-proton Exchanger Isoform 3 (Nhe3) By Pkmentioning
confidence: 99%
“…Third, sulphonylureas enhance exocytosis as measured by an increase in b-cell membrane capacitance (Hoy et al 2000). Fourth, the ability of cyclic AMP to potentiate insulin exocytosis in a PKA-independent manner is impaired in SUR1 knockout mice (Nakazaki et al 2002). This may be related to the fact that Epac (cAMP-GEFII ) specifically binds to NBD1 of SUR1 in a cAMP-dependent manner (Shibasaki et al 2004a).…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…Doliba et al [41] and Nakazaki et al [106] reported that acetylcholine and carbachol stimulate insulin release from Sur1KO islets even in low glucose. Doliba et al [41] argue secretion is impaired in the Sur1KO mice and suggest acetylcholine, released in response to feeding, enhances insulin secretion, thus contributing to their euglycemia.…”
Section: Acetylcholine and Amino Acidsmentioning
confidence: 99%
“…Shiota et al [137] showed that Sur1KO mice failed to increase their plasma insulin in response to exogenous GLP-1, and Nakazaki et al [106] demonstrated that, whereas GLP-1, gastric inhibitory peptide (GIP), and exendin 4 increased the cAMP level in isolated islets, their potentiation of glucose-stimulated insulin release was reduced. The impaired incretin response was secondary to a blunted response to elevated cAMP acting via a protein kinase A (PKA)-independent pathway [48,106]. The impaired response was specific for cAMP, and Sur1KO islets were stimulated by carbachol, a nonhydrolyzable analog of acetylcholine, and by tissue plasminogen activator (TPA), a protein kinase C (PKC) activator.…”
Section: The Incretin Response Is Impaired In Sur1ko Micementioning
confidence: 99%